Computed tomography features of luetic osteitis (otosyphilis) of the temporal bone. Issue 2 (February 2014) - Ogungbemi, A; Dudau, C; Morley, S; Beale, T
Abstract Objective: We report a missed case of otosyphilis presenting as otic capsule lucencies on temporal bone computed tomography. Methods: A 58-year-old woman presented with a 15-year history of bilateral, mixed hearing loss together with otic capsule lucencies, subsequently confirmed as otosyphilis. A literature review of otosyphilis was undertaken based on a PubMed search of studies published between 1988 and 2012, using the key words 'otosyphilis', 'otodystrophy', 'otic capsule lucencies' and 'luetic osteitis'. Results and conclusion: Although rare, otosyphilis is important to recognise as it is one of the few treatable causes of deafness when diagnosed early. The differentiating computed tomography features of luetic osteitis (otosyphilis) of the temporal bone have only rarely been described. We emphasise how these imaging features can be used to distinguish the rare but treatable condition of luetic osteitis from other, more common conditions with similar imaging findings.